2021
DOI: 10.3390/genes12040546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Population Structure of Polish Konik Horse Maternal Lines Based on Microsatellite Markers

Abstract: Summary: The aim of this study is to reveal the genetic variability and population structure of maternal lines of the Polish Konik—a native Polish horse breed of the primitive type included in the Polish conservation programme. The analysis was carried out on the basis of 17 microsatellite markers routinely used for parentage testing. The structural analysis indicated the likelihood of three genetic clusters (using the Structure and Structure Harvester software). F-statistics indicated a low level of inbreedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Recently, many studies have been focused on the loss of biodiversity [ 23 , 24 , 25 ] or the increase in deleterious genotypes [ 26 ] caused by such inbreeding (as reviewed in [ 7 ]). In the last 200 years, the inbreeding practice led to the phenotypical expression at homozygous sites of deleterious variants [ 27 ], as highlighted when the coefficients are calculated in order to evaluate the genetic diversity among different horse breeds [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have been focused on the loss of biodiversity [ 23 , 24 , 25 ] or the increase in deleterious genotypes [ 26 ] caused by such inbreeding (as reviewed in [ 7 ]). In the last 200 years, the inbreeding practice led to the phenotypical expression at homozygous sites of deleterious variants [ 27 ], as highlighted when the coefficients are calculated in order to evaluate the genetic diversity among different horse breeds [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cieślak et al (2017) , for the first time, suggested that mtDNA results do not fully correspond to the official pedigree data. Another study focused on assessing the genetic diversity and structure of the Polish Konik breed based on 17 microsatellite markers ( Fornal et al, 2021 ), and this presented no signs of inbreeding and the assignment of the horses using Structure software into (most likely) three clusters. However, the study conducted by Mackowski et al (2015) found 8.6% of inbreeding.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the genetic diversity and genetic structure of small biological populations is crucial for protecting their genetic diversity and the uniqueness of the gene pool [ 30 ]. Golden-backed carp cultivation is ongoing, but basic research and reports on their genetic breeding are very scarce; therefore, we studied the current state of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%